The Effect of Awareness of Paying Taxes, Tax Sanctions on Willingness to Pay Income Tax in Tabalong Regency - Analisa; Nurhidayah, Lilik (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
This research is a field research, quantitative in nature which has two independent variables, namely Awareness of Paying Taxes (X1), Tax Sanctions (X2), and using one dependent variable, namely Willingness to Pay Taxes (Y). This study aims to determine: (1) The effect of Awareness of Paying Taxes and Tax Sanctions Simultaneously on Willingness to Pay Taxes. (2) the influence of Awareness of Paying Taxes and Tax Sanctions partially on Willingness to Pay Taxes. The population of this research is the taxpayer on income tax in Tabalong Regency. The sample using Convenience Sampling is 100 respondents. Data collection techniques using a questionnaire. The collected data were analyzed using validity test, reliability test, classical assumption test, and multiple regression. The results of this study indicate that: (1) there is no positive and significant effect on Awareness of Paying Taxes, Tax Sanctions on Willingness to Pay Taxes. Shown by the value of Fcount 1.120 < Ftable 2.70 and with a significance (0.345 > 0.050), (2) there is no positive and significant effect of Awareness of Paying Taxes on Willingness to Pay Taxes. Shown by the value of -0.358 < 1.66088 and with a significance (0.721 > 0.050), (3) There is no positive and significant effect of Tax Sanctions on Willingness to Pay Taxes. It is indicated by a value of 0.143 < 1.66088 with a significance (0.137 > 0.050).